Investing in Urban Resilience : Protecting and Promoting Development in a Changing World - World Bank Group (World Bank, Washington, DC, 2016)
Cities in the developing world are rapidly expanding, boosting countries’ economies, reducing poverty, and fueling global prosperity. But as more people, assets, and economic activity become concentrated in cities, and infrastructure struggles to keep up with rapid growth, the risk posed by natural disasters and climate change is rising. The urban poor – who are most exposed and least able to cope – will be hardest hit, with up to 77 million urban residents potentially falling back into poverty as a result of climate change alone. To help the urban poor unlock their full economic potential and protect hard-won development gains, the report discusses the need to invest in urban resilience. Over the next 15 years, at least 400 billion dollars will be needed each year to make city infrastructure low-emissions and more resilient to the wide range of shocks and stresses that cities may encounter. The flagship report -- co-authored by the World Bank Group and the Global Facility for Disaster Reduction and Recovery -- illustrates how building urban resilience is critical to reducing poverty and promoting shared prosperity. And while, over the last five years, the World Bank Group has financed more than $9 billion in projects to help cities in 41 countries become more resilient, significant investment gaps remain. To overcome these gaps, the World Bank Group and other multilateral development institutions can play a critical role in enabling city and national governments leverage private